Effect of Triphala Kajjali tablet - an Ayurvedic herbomineral formulation for the management of metabolic syndrome: a single case study - Garasia, Jaynika S.; Goyal, Mandip (International Journal of Advances in Medicine, 2021)
Metabolic syndrome (MS) is a group of disorders that includes abdominal obesity, diabetes, hypertension, and elevated cholesterol. Approximately 25% of the adult populations are affected by MS. Gradually this number is increasing because of poor lifestyles, faulty dietary pattern, physical inactivity, stressful life and rapid urbanization. A 50-year-old female patient visited to OPD of Kayachikitsa department ITRA, Jamnagar, with the complaints of gradual weight gain with excess body fat around the abdomen and waist region, numbness and burning sensation at bilateral feet, and breathlessness on exertion. After investigation, she was diagnosed as a case of MS as per National Cholesterol Education Program (NCEP), adult treatment panel III (revised in 2005) guideline. She was treated with Triphala Kajjali tablet for 12 weeks along with lifestyle modification. After completion of treatment, investigations revealed reduction in fasting blood sugar from 113 mg/dL to 80 mg/dL, serum cholesterol level was decreased to 148 mg/dl from 216 mg/dl, serum triglycerides level was reduced to 150 mg/dL from 187 mg/dL and serum LDL was reduced to 68.3 mg/dl from 118.7 mg/dl. Her weight reduced to75 kg from 85 kg, and waist circumference reduced to 92 cm from 100cm, and blood pressures also reduced up to 122/82 mmHg from 140/90 mmHg. Hence, it can be concluded that Triphala Kajjali tablet along with lifestyle modification are effective in the management of MS, as it possesses Kapha Medohara properties.